Comprehensive Sexuality Education (CSE) in India: Decoding Parental Views and Understanding - Likith R S; Vigneshwaran Subbiah Akkayasamy (Journal of Psychosexual Health, 2026)
Objectives: To explore parental attitudes toward comprehensive sexuality education (CSE), assess their willingness to discuss sexuality-related topics with their children, and generate evidence to support policy advocacy for age-appropriate CSE in Indian schools. Method: A cross-sectional quantitative study was conducted among 113 parents from rural and urban India using a self-administered questionnaire. Descriptive analysis was performed. Results: Parents generally expressed positive attitudes toward CSE; however, stigma persisted around discussing consent, contraception, sexually transmitted infections, gender identity, and sexual orientation. Although parents acknowledged their responsibility, many lacked preparedness and confidence. Family and community support was largely absent, with prevailing stigmatic beliefs reinforcing communication barriers. Preference for teachers or healthcare professionals as CSE providers was also low. Conclusion: Despite increasing acceptance of CSE, strengthening age-appropriate school-based CSE, parent capacity-building, community sensitization, and school-family collaboration is essential to overcome socio-cultural barriers and promote children’s safety, well-being, and holistic development.